Research on Fano Resonance Sensing Characteristics Based on Racetrack Resonant Cavity - Yaxin Yu (MDPI AG, 2021)
To reduce the loss of the metal–insulator–metal waveguide structure in the near-infrared region, a plasmonic nanosensor structure based on a racetrack resonant cavity is proposed herein. Through finite element simulation, the transmission spectra of the sensor under different size parameters were analyzed, and its influence on the sensing characteristics of the system was examined. The analysis results show that the structure can excite the double Fano resonance, which has a distinctive dependence on the size parameters of the sensor. The position and line shape of the resonance peak can be adjusted by changing the key parameters. In addition, the sensor has a higher sensitivity, which can reach 1503.7 nm/RIU when being used in refractive index sensing; the figure of merit is 26.8, and it can reach 0.75 nm/°C when it is used in temperature sensing. This structure can be used in optical integrated circuits, especially high-sensitivity nanosensors.